Peningkatan Pengetahuan Tentang Penyakit Degeneratif Pada Masyarakat Petani di Desa Laliko Sulawesi - Hafsah Hafsah; Hasria Alang; Hastuti Hastuti; Muh. Sri Yusal (UNIB Press, 2022)
Degenerative disease is a disease that commonly occurs due to increasing age, so that the function of the body's organs decreases in function. This disease is also triggered by an unhealthy lifestyle, such as poor diet and lack of physical activity. This causes degenerative diseases not only suffered by the elderly, but also occurs in someone at an early age. Some cases of degenerative diseases can cause patients to undergo treatment and even complications that can lead to death. This is the reason the community service team took the theme of degenerative disease education and made Laliko Village a partner for this activity. The method of activity is through lectures with the help of powerpoint using an LCD. Analysis of the data using a comparison of the initial test and the final test. The initial stage is done by giving a test in the form of questions orally, this is intended to see the understanding of the participants. Furthermore, providing education about degenerative diseases. The last stage is giving questions as a final test. This serves to measure the knowledge of participants after being given education. The results of the service show that there has been an increase in the knowledge of the participants, which can be seen from the ability of the participants to respond or answer correctly the questions posed by the service presenters. This service activity went smoothly because of the positive support from partners and good cooperation between partners and the service team.